Strategi Pengembangan Infrastruktur Jaringan Air Bersih Di Kecamatan Mamasa Kabupaten Mamasa - Sabta, Roynardi; Aksa, Kamran; Idris Taking, Muhammad (Fakultas Teknik Universitas Bosowa, 2024)
The purpose of this research is to formulate a strategy for the development of clean water network infrastructure in Mamasa District, in order to meet the domestic clean water needs of the community through a clean water network system. The approach used in this research is a qualitative approach. The analysis used is descriptive and SWOT analysis. Descriptive analysis is carried out on aspects that affect the limited supply of clean water, while SWOT analysis is used to look for development strategies by identifying strengths, weaknesses, opportunities and threats. The strategy that needs to be carried out to develop clean water network infrastructure in Mamasa District to meet the community's clean water needs is the need for maintenance and maintenance around water catchment areas and rivers which are sources of raw water on a regular basis, it is necessary to add new IPA with a processing capacity of 50 Liters / second, whose source of raw water is one of the rivers in Tondok Bakaru Village, as well as making a feasibility study on strategic routes for transmission or distribution pipelines taking into account the topographical conditions of the area.